Contralateral pneumothorax, pneumomediastinum, and pneumopericardium after dual-chamber pacemaker implantation - Mariana Pereira Santos; André Alexandre; Maria João Sousa; Severo Torres (Indian Pacing and Electrophysiology Journal, 2025)
We present a rare case of a 79-year-old man who developed contralateral pneumothorax, pneumomediastinum, and pneumopericardium following dual-chamber pacemaker implantation for symptomatic second-degree atrioventricular block. The procedure itself was uneventful, with appropriate lead placement and good electrical parameters.However, 30 minutes post-procedure, the patient developed right-sided pleuritic chest pain and dyspnea. Imaging revealed a right-sided pneumothorax, pleural effusion, pneumomediastinum, and pneumopericardium. A chest drain was inserted due to the significant pneumothorax volume, leading to symptom resolution. Electrocardiographic changes and inflammatory marker elevation suggested pericarditis, which was successfully treated with ibuprofen and colchicine. The patient was discharged after 13 days and remained stable at a 1-year follow-up.The suspected mechanism of injury was atrial lead perforation, although other causes, such as pleural puncture or superior vena cava injury, were considered. Management of such cases varies, with lead revision being unnecessary in this patient due to stable pacing parameters. This case highlights an unusual complication of pacemaker implantation and underscores the importance of prompt diagnosis and individualized management.